A randomised controlled trial to assess the clinical effectiveness and cost-effectiveness of alternative treatments to Inhibit VEGF in Age-related choroidal Neovascularisation (IVAN) - Chakravarthy, U; Harding, SP; Rogers, CA; Downes, S; Lotery, AJ; Dakin, HA; Culliford, L; Scott, LJ; Nash, RL; Taylor, J; Muldrew, A; Sahni, J; et al. (NIHR Journals Library, 2015)
Background Bevacizumab (Avastin®, Roche), which is used in cancer therapy, is the ‘parent’ molecule from which ranibizumab (Lucentis®, Novartis) was derived for the treatment of neovascular age-related macular degeneration (nAMD). There were reports in the literature on the effectiveness of bevacizumab in treating nAMD, but no trials. The cost per dose of bevacizumab is about 5–10% that of ranibizumab. This trial was a head-to-head comparison of these two drugs.